A multimodel ensemble machine learning approach for CMIP6 climate model projections in an Indian River basin. (4th August 2022) - Dey, Aiendrila; Sahoo, Debi Prasad; Kumar, Rohini; Remesan, Renji
Abstract: Multimodel ensemble (MME) approach would help modellers to know the advantages of individual global circulation models (GCMs) and to avoid the weaknesses associated with them, and it would help the river basin modellers to make appropriate modelling decisions. The study highlights the river basin‐scale development of MME as a convenient way to reduce the parameter and structural uncertainties in the Coupled Model Intercomparison Project Phase 6 (CMIP6) GCMs simulations after identifying the best five CMIP6 GCMs based on the rating metric calculations. Furthermore, the performance of the MME was enhanced by integrating three machine learning algorithms (artificial neural network [ANN], random forest [RF], support vector machine [SVM]). Subsequently, comparative assessment depicted the improved performance in MME‐integrated ML algorithms compared to simple arithmetic mean (SAM) in simulating observed precipitation ( P ), maximum temperature ( T max ), and minimum temperature ( T min ) over the Damodar River basin (DRB), India. The statistical metrics indicate that the SVM and RF methods yielded better results than SAM and ANN methods, thus selected for future projections. The robustness of the MME‐RF and MME‐SVM approach has also been observed while capturing the spatial pattern as IMD‐observed with well representation of climate indices for both wet and dry seasons. Future projections with MME‐SVM and MME‐RF suggested a possible rise in mean annual P in the range of 1.4–15% and 6.8–39% with an increasing trend in temperature ( T max, T min ) under the SSP245 and SSP585 scenarios, respectively. Replicating the spatial pattern of the future climatic variables projections evinced a warmer and drier climate in the southwest part of the DRB for both SSP scenarios during wet and dry season and thence warned a probable drier condition on the southwest part of the DRB in future time slices. Abstract : Evaluated MME‐ML model's basin‐scale projections for SSP245 and SSP585 scenarios. Spatiotemporal dynamics of MME of CMIP6 in Damodar River basin was investigated. SVMs and RFs are good for MMEs at river basin scale and better than SAM. Taylor skill score suggests MPI‐ESM‐1‐2‐HR and CanESM5 as the best and poor models.